Starch/MWCNT/epoxy composites for biodegradable batteries - Ansari M.N.M.; Shanks R.A.; Kong I. (2023)
In this paper, the preparation of starch/multi-walled carbon nanotubes (MWCNTs)/epoxy composite and electrical properties of the composites were discussed. The introduction of MWCNTs restrained starch re-crystallization, improved the thermal stability of the starch/epoxy composites, improved modulus. From the thermal studies, the presence of starch promotes the degradability of the composites. However, the optimum loading of the starch in the composite has not been covered. The composites exhibited a low electrical percolation threshold of 0.05-0.10 wt% of MWCNTs which can be observed from the log P ?, Vs MWCNT loadings curve and show improved conductivity of the composite with less than 0.1 wt% of MWCNTs and 1wt% of starch content. There was amarginal increase in the capacitance of the composites upon the addition of MWCNT.